Association between dietary niacin intake and abdominal aortic calcification among the US adults: the NHANES 2013–2014 - Zhang, Jiqian; Li, Ming; Wang, Xinyi; Wang, Tongxin; Tian, Wende; Xu, Hao (Frontiers in Nutrition, 2024)
Background Abdominal aortic calcification (AAC) serves as a reliable predictor of future cardiovascular incidents. This study investigated the association between dietary niacin intake and AAC in US adults. Methods In this study, we conducted a cross-sectional study of 2,238 individuals aged 40 years and older using data from the National Health and Nutrition Examination Survey (NHANES) 2013–2014. AAC was evaluated using the Kauppila scoring system through dual-energy X-ray absorptiometry. Daily niacin intake was calculated by averaging the two dietary recalls and classified in tertiles for analysis. In this study, multiple regression analyses and smoothed curve fitting were used to examine the relationship between dietary niacin intake and AAC, subgroup analyses and interaction tests were used to assess the stability of this relationship across different segments of the population, and forest plots were used to present the results. In addition, we validated the predictive performance of dietary niacin intake on the risk of severe AAC through Receiver Operating Characteristic (ROC) curve analysis. Results Among 2,238 participants aged >40 years, the results showed that the higher dietary niacin intake group was associated with lower AAC score (β = −0.02, 95% CI: −0.04 – −0.01), and a lower risk of severe AAC (OR = 0.97, 95% CI: 0.96–0.99). In the fully adjusted model, the higher tertile group was associated with lower AAC score (β = −0.37, 95% CI: −0.73 – −0.02; P for trend = 0.0461) and a lower risk of severe AAC (OR = 0.60, 95% CI: 0.38–0.93; P for trend = 0.0234). The relationship between dietary niacin intake and AAC differed significantly between diabetic and non-diabetic population. The ROC curve analysis revealed that the area under the curve (AUC) for predicting severe AAC risk based on dietary niacin intake was 0.862, indicating good predictive performance. Conclusion Higher dietary niacin intake group was associated with lower AAC score and a lower risk of severe AAC. Our findings suggest that dietary niacin intake has the potential to offer benefits in preventing AAC in the general population.